Mechanisms of Immune Evasion in Multiple Myeloma: Open Questions and Therapeutic Opportunities - Botta, Cirino; Mendicino, Francesco; Martino, Enrica Antonia; Vigna, Ernesto; Ronchetti, Domenica; Correale, Pierpaolo; Morabito, Fortunato; Neri, Antonino; Gentile, Massimo (Cancers, 2021)
Multiple myeloma (MM) is the second most common hematologic malignancy, characterized by a multi-step evolutionary path, which starts with an early asymptomatic stage, defined as monoclonal gammopathy of undetermined significance (MGUS) evolving to overt disease in 1% of cases per year, often through an intermediate phase known as “smoldering” MM (sMM). Interestingly, while many genomic alterations (translocation, deletions, mutations) are usually found at early stages, they are not sufficient (alone) to determine disease evolution. The latter, indeed, relies on significant “epigenetic” alterations of different normal cell populations within the bone marrow (BM) niche, including the “evasion” from immune-system control. Additionally, MM cells could “educate” the BM immune microenvironment (BM-IM) towards a pro-inflammatory and immunosuppressive phenotype, which ultimately leads to disease evolution, drug resistance, and patients’ worse outcome. Indeed, it is not a case that the most important drugs for the treatment of MM include immunomodulatory agents (thalidomide, lenalidomide, and pomalidomide) and monoclonal antibodies (daratumumab, isatuximab, and elotuzumab). On these bases, in this review, we describe the most recent advances in the comprehension of the role of the different cells composing the BM-IM, and we discuss the potential molecular targets, which could represent new opportunities to improve current treatment strategies for MM patients.